The Point of View of Today's Alevism Towards Dedeism that is Accepted as Social-Religious Authority by Alevi Society in the Historical Period in Terms of Malatya Case - Ozdemir, Suayip (Gazi Univ, Turk Kulturu ve Haci Bektas Veli, 2008)
Dedeism is an association which has an important role to enable Alevism to reach today and it has a great role in the social and religious structuring of this tradition. Some of our subjects in investigation are that the dedes who have an important role in Alevism are needed for the continuance of Alevism that dedes must be descended from the same root, and these dedes should be educated. The technique of questionnaire was used in our investigation. The aim of this study that handles the point of views of our citizens about dedes is to reveal the thoughts of our Alevi citizens about the dedes, to clarify their expectation from the dedes, and to develop some ideas about the education of dedes.
Keywords: Association of Dedeism; Malatya; Alevi society; the technique of questionnaire